Teacher Professional Development in the Context of Independent Learning - Riska Nadia (Nusantara Education, 2023)
In response to the demands of competence and learning in the era of the Industrial Revolution 4.0, the Ministry of Education and Culture of the Republic of Indonesia introduced the Merdeka Belajar (Freedom to Learn) policy as a strategic effort to enhance educational quality. This policy emphasizes the exploration of teachers’ and students’ potential to foster innovation and independent learning. Central to this framework is Merdeka Mengajar (Freedom to Teach), which grants teachers professional autonomy to design and implement effective learning practices. This study aims to examine the significance of teacher professional development in supporting the successful implementation of Merdeka Mengajar within contemporary educational contexts. This research employs a qualitative approach using a literature review method. Data were collected through documentation of policy papers, academic publications, and relevant reports on teacher development and educational reform. The analysis was conducted using thematic content analysis to identify key patterns and conceptual relationships between professional autonomy, teacher competence, and learning outcomes. The findings reveal that the successful implementation of Merdeka Mengajar is highly dependent on continuous and context-sensitive professional development. Teachers are required to function as lifelong learners who are adaptive to rapid advancements in science and technology. School-based teacher professional development emerges as the most effective model, as it aligns closely with teachers’ real needs, classroom challenges, and institutional contexts. Moreover, this approach fosters the formation of professional learning communities, enabling collaborative reflection, knowledge sharing, and sustained improvement in teaching practices. This study contributes to the academic discourse by proposing a contextualized framework for teacher professional development that supports educational transformation. It underscores the importance of integrating autonomy, collaboration, and continuous learning to strengthen teacher professionalism and improve student learning outcomes in a rapidly evolving educational landscape.